ESTRUCTURA EPIDERMICA DE ARAUCARIA NATHORSTI DUS. DEL TERCIARIO DE PICO QUEMADO, RIO NEGRO (Ameghiniana, 2013)
The epiderrnal structure of Arauearía nathorsti Dus from the Tertiary of Pico Quemado, Río Negro (Argentina). The epidermal structure of leaves of Araucaría nathorsti Dus. collected in Tertiary sediments (Patagoniense) from Pico Quemado western Río Negro province (41Qº35' lato and 71º W long), shows close aHinity with the epidermal structure of the living species Araucaria araucana, differing only in few detaíls.